2017
DOI: 10.1002/ardp.201700234
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, in silico and antiproliferative evaluation of novel pyrazole derivatives as VEGFR‐2 inhibitors

Abstract: As the blockade of the VEGFR-2 signaling pathway is a viable approach in cancer therapy, the present study focuses on a series of pyrazole based VEGFR-2 inhibitors that were designed on the basis of the hybridization approach, supported by docking and in silico computational studies. The designed compounds were synthesized through facile synthetic methods and the structures were K E Y W O R D Santiproliferative activity, molecular modeling, synthesis, VEGFR-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…[15,20] Many phthalazine derivatives were reported to have VEGFR-2 and EGFR kinase inhibitory activities, with IC 50 values in the nanomolar range; however, compounds were more selective and better inhibitors of VEGFR-2 compared with EGFR. [21,22] Other pharmacophoric heterocycles have been implanted in the structures of recently reported anticancer agents with a VEGFR-2 inhibitory effect, for example, pyrazole [23,24] and pyrimidine. [25,26] The latter were reported to have spatial configurations that enable both to interact with the VEGFR-2 binding site.…”
Section: Introductionmentioning
confidence: 99%
“…[15,20] Many phthalazine derivatives were reported to have VEGFR-2 and EGFR kinase inhibitory activities, with IC 50 values in the nanomolar range; however, compounds were more selective and better inhibitors of VEGFR-2 compared with EGFR. [21,22] Other pharmacophoric heterocycles have been implanted in the structures of recently reported anticancer agents with a VEGFR-2 inhibitory effect, for example, pyrazole [23,24] and pyrimidine. [25,26] The latter were reported to have spatial configurations that enable both to interact with the VEGFR-2 binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the same compound exhibited the highest VEGFR-2 inhibitory activity with an IC 50 value of 1.89 mM. 166 The in vitro and in vivo results collectively suggest that 174 (Fig. 7), a new type of signal transducer and activator of transcription (STAT)3 inhibitors based on structural modications on shikonin scaffold, guided by computational modeling, may serve as a promising lead compound for the further development of potential therapeutic anti-neoplastic agents.…”
Section: Computer-aided Synthesis Of Compoundsmentioning
confidence: 91%
“…Chimento et al, 145 reported the synthesis of some new titanocene and half-titanocene compounds having a methyl group on the carbon 6 and a methoxy-naphthyl group as substituent of the cyclopentadienyl. Moreover, the IC 50 values of the most active compounds (i.e., [164][165][166] and of cisplatin have been calculated, evidencing that these new complexes 164-166 (IC 50 value of 85.26, 49.16 and 129.8 mM respectively for MCF-7) exerted antiproliferative effect on MCF-7 BC cells, via inhibiting important DNA-metabolizing enzymes, that is, topoisomerase I and II (Table 7).…”
Section: The Titanocene Functional Groupmentioning
confidence: 93%
“…After 3 h incubation at 37 °C, 100 μL of DMSO was added to each well, and the plate was agitated for 1 min. The absorbance was read at 570 nm with a multi‐well plate reader (Victor3, PerkinElmer), and IC 50 values were calculated .…”
Section: Methodsmentioning
confidence: 99%